Impact of body height and weight on specific motor abilities of volleyball players - Pocek, S.; Vukovic, M. (3rd International Scientific Conference: Exercise and quality of life. April 12/13th 2013, 2013)
Effective and efficient movement is fundamental to sports performance. Movement binds together all of the skills of a game into a coherent flow. Sport - specific training program can induce peculiar neuromechanical adaptations that are commonly considered as signs of aquisition and/or improvement of a specific movement skill. An athlete`s anthropometric and physical characteristics may represent important prerequisites for successful participation in any given sport. Twenty one collegiate volleyball players, (age 19.85 +/- 0.83 years; height 181.67 +/- 12.03 cm; weight 72.62 +/- 12.99 kg; training experience 6.76 +/- 2.21 years), were recruited for this study. The purpose of this study was to examine the significance of the impact of body height and weight on the specific motor abilities of volleyball players. The following tests were performed: Block jump, Spike jump, Standing broad jump, Jelka test, T- test, 93639 m test, Obstacle course backwards, Arm plate tapping and Dash 20 m. Regression analysis from package SPSS 15.0 was used for data processing. The results showed that body height and weight had a statistically significant impact on the expression of specific motor abilities of volleyball players. Indeed, it can be assumed that an athlete`s anthropometric characteristics can in some way influence his/her level of performance, at the same time helping to determine a suitable physique for a certain sport.